NILAI-NILAI OPTIMISME DALAM ISTI’ADZAH DAN BASMALAH (STUDI TAFSIR AR-RAZI) - Yuzaidi, Yuzaidi; Sari, Winda (UIN Sumatera Utara Medan, 2019)
This article examines the values of optimism contained in isti'adzah and basmalah. The object of the study is the Book of Tafsir ar-Razi (Mafatih al-Ghaib) by Imam Fakhr ad-Din ar-Razi. This interpretation tends to be philosophical. In interpreting isti'adzah and basmalah, he tried to explore the wisdom implied in it so that it had an association with optimism. Among them that the most pronunciation of main ( afdhal) is a’udzu instead of asta'idzu even though the clause of the verse mentions fasta'idz (ask for protection). Because a'udzu is a pledge that describes the condition of an optimistic servant who has entered the protection of God Almighty. In addition to the basmalah pronunciation there is a deleted word (mahdzuf), namely: bismillah ibtada `kullu syai`. A parable is revealed about the king's slave who bought several horses, camels or donkeys by labeling the king's name on the shoulders of the animal so that the enemies could not disturb him. In this case it is as if Allah Almighty. said